Impact of polyvinyl chloride, polystyrene, and polyethylene on the organism of mice - M. A. Lieshchova; V. V. Brygadyrenko; N. M. Tishkina; P. M. Gavrilin; A. A. Bohomaz (Regulatory Mechanisms in Biosystems, 2019)
Goods of plastic, due to their durability, universality and economical properties are broadly used in all spheres of life. On the whole, polymers are inert and nontoxic, but in the process of their production, various additives are used, which on contact or introduction into an organism has a negative effect on it. In our study, we determined the impact of some types of plastic (polyvinyl chloride, polysterene and polyethylene) on the organism of laboratory animals according to changes in their body weight, indices of mass of the internal organs, and blood parameters. For the experiment, we formed four groups of white male mice at the age of 3 weeks and average body weight of 50 g. For each group, we used different litter. For group I, the litter was sawdust; and for the other groups we added plastic products in different volumes to the sawdust; for group II finely cut polyvinyl chloride, for group III cut polyethylene, and for group IV granules of polystyrene. Every 3 days, we determined the body weight of the animals, and 32 days later we determined mass of the organs, clinical and biochemical parameters of the blood. Addition of polyvinyl chloride, polyethylene, and polystyrene into the substrate for mice did not have a significant effect on tempi of growth of body weight, and also relative mass of heart and lungs. Polyvinyl chloride and polystyrene have an immune-suppressive effect, and polyvinyl chloride affects both central and peripheral organs, and polystyrene mostly harms the peripheral organs. All used types of plastic cause leukocytopenia, following which neutrophilia of band neutrophils and monocytosis takes place as a result of damage to the biological barriers. We determined the systemic toxic effect of the studied types of plastic on the internal organs, which manifested in increase in their mass (liver, kidneys), steep increase in the activity of liver enzymes (AST, ALT), simultaneous decrease in activity of alkaline phosphatase and content of cholysterol and glucose in the blood serum of the mice. Also polyvinyl chlorine, polyethylene and polystyrene cause degeneration of the epithelium of the uriniferous tubule, which is manifested in reduction of globulins and creatinine in the blood of animals from the experimental groups following increase in relative mass of the kidneys. The results of our research allow us to state that different types of plastic can cause toxic effect on animals, as well as people who are in frequent contact with them.